ASSESSMENT AND RANKING OF LIQUIDITY OF SERBIAN AGRICULTURAL ENTERPRISES - Ševkušić, Ljubiša; Bodiroga, Radomir; Vukoje, Veljko (Journal of Agricultural Sciences (Belgrade), 2022)
The key task of all enterprises, regardless of the activity they are engaged in, is constant growth and development. This is a prerequisite for survival in the modern market. Continuous monitoring and analysis of all production and financial performance of the enterprise is extremely important, with liquidity as the most important. Liquidity is a very important indicator of the overall financial condition of the company and is the most urgent requirement that is placed before modern companies. The focus of this research is on the financial performance of enterprises that according to the official classification of activities belong to sector A - Agriculture, forestry and fisheries. The aim of this paper is to evaluate the liquidity of these companies and perform the ranking by applying the modern method of multi-criteria decision-making MABAC. The results of the research clearly show that the liquidity of the agricultural sector of Serbia is not at a satisfactory level, and the best results were recorded during 2019.